Assessing the capacity of primary health care facilities in Nigeria to deliver eye health promotion: Results of a mixed-methods feasibility study. - Ada Aghaji; Helen E D Burchett; Shaffa Hameed; Clare Gilbert (Public Library of Science (PLoS), 2022)
Over 25 million people in sub-Saharan Africa are blind or visually impaired, the majority from avoidable causes. Health promotion and disease prevention are important strategies for eye health, through good governance, health literacy and increasing access to eye care services. To increase equity in access for eyecare services, the World Health Organization Africa Region developed a package of interventions for primary eye care, which includes health promotion. The aim of this study was to assess the capacity of the primary healthcare system to deliver health promotion for eye care in Nigeria. Mixed methods were used during a survey of 48 government-owned primary health care facilities in Anambra state, Nigeria: interviews with district health supervisors, facility staff and village health workers, and a desk review of policy documents for primary health care and eye care in Nigeria. Findings were benchmarked against the capacities needed to deliver health promotion agreed through a Delphi exercise and were analysed using the World Health Organization's health system building blocks. Eye health promotion policies exist but are fragmented across different national health policies. Health promotion activities focussed on "mobilising" community members to access care provided in facilities, particularly for women of childbearing age and young children, and health education was limited. Only one in ten facilities engaged the elderly and a fifth delivered health promotion for eye care. Health promotion activities were supervised in 43.2% of facilities and transport to remote areas was limited. A robust eye health promotion strategy needs to be included in the National Eye Health Policy. The scope of existing health promotion will need to expand to include eye conditions and different age groups. Increasing eye health literacy should be emphasized. Governance, training health workers in eye health promotion, educational materials, and transport to visit communities will also be needed.